Ethical Analysis Of Dark Pattern Marketing On The Shopee E-Commerce Platform Among University Students In Makassar City - Nulthazam Sarah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The digitalisation of commerce has introduced the phenomenon of dark pattern marketing, which manipulates consumer decisions through strategic interface design. This research explores the implementation, perception, and ethical implications of dark patterns on the Shopee platform for university students in Makassar City, who are active digital consumers. Using a descriptive qualitative approach with semi-structured interviews of ten active Shopee-using students, the study identified six dominant dark pattern categories: false urgency, hidden costs, forced continuity, confirm shaming, trick questions, and obstruction. Findings show false urgency is the most prevalent tactic, affecting all participants and creating a 'fear of missing out' that drives impulsive purchases. A paradox of awareness was revealed, where only 40% of students recognised the design manipulation, despite being highly educated digital natives. The economic impact reaches IDR 150,000–IDR 400,000 per month per individual through overspending and unplanned purchases. The ethical implications indicate fundamental breaches of the principles of honesty, transparency, and consumer autonomy, resulting in significant erosion of trust, with 60% of participants stating an intention to reduce their shopping activity. This research affirms that dark patterns are not merely a technical issue but a business ethics problem threatening the sustainability of the e-commerce ecosystem. Recommendations include the adoption of ethical design by platforms, strengthening digital consumer protection regulations, integrating consumer literacy into higher education, and multi-stakeholder collaboration to create a fair and transparent digital ecosystem.